Видатний мислитель ХХ століття (до 150-річчя з дня народження В. І. Вернадського) - Арцишевський, Роман; Artsishevskiy, Roman (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено головні філософські ідеї В. І. Вернадського, які характеризують його як видатного мислителя ХХ ст. The article deals with the questions of the main V. I. Vernadskiy’ philosophical ideas wich characterized him as outstanding thinker of the ХХth century. It is considered tye philosophical preconditions of yis studies about biosphere and noosphere, the problems of correlation among science, philosophi and religion, its role in working out the scientific world outbook, scientist’ responsibility, the idea of integrity of modern mankind and unity of yistorical process.
Outstanding Thinker of the ХХth Century (to the 150th Year of the V. I. Vernadskiy’ Birth-Day)
Keywords: біосфера; biosphere; ноосфера; noosphere; картина світу; picture of the world; світогляд; world outbook; наука; science; релігія; religion; філософія; philosophy